The Sensitive Nature of Social Trust to Intelligence - Oasis Kodila-Tedika; Simplice Asongu; Florentin Azia-Dimbu (African Governance and Development Institute (AGDI), 2016)
This study investigates the relationship between social trust and intelligence. The extreme bound analysis of Levine and Renelt is employed to directly assess the strength of the nexus. The findings confirm the positive and robust nexus between social trust and intelligence. We have contributed to the literature by confirming that the previously established positive linkage between intelligence and trust is not statistically fragile. In fact the nexus withstands further empirical scrutiny with more robust empirical strategies.
Keywords: G20; I20; I29; J24; P48; Z13; 330; Trust; Intelligence; Human Capital; Extreme Bound Analysis